A Dual Immunotherapy Nanoparticle Improves T‐Cell Activation and Cancer Immunotherapy. Issue 25 (25th April 2018) - Mi, Yu; Smith, Christof C.; Yang, Feifei; Qi, Yanfei; Roche, Kyle C.; Serody, Jonathan S.; Vincent, Benjamin G.; Wang, Andrew Z.
Abstract: Combination immunotherapy has recently emerged as a powerful cancer treatment strategy. A promising treatment approach utilizes coadministration of antagonistic antibodies to block checkpoint inhibitor receptors, such as antiprogrammed cell death‐1 (aPD1), alongside agonistic antibodies to activate costimulatory receptors, such as antitumor necrosis factor receptor superfamily member 4 (aOX40). Optimal T‐cell activation is achieved when both immunomodulatory agents simultaneously engage T‐cells and promote synergistic proactivation signaling. However, standard administration of these therapeutics as free antibodies results in suboptimal T‐cell binding events, with only a subset of the T‐cells binding to both aPD1 and aOX40. Here, it is shown that precise spatiotemporal codelivery of aPD1 and aOX40 using nanoparticles (NP) (dual immunotherapy nanoparticles, DINP) results in improved T‐cell activation, enhanced therapeutic efficacy, and increased immunological memory. It is demonstrated that DINP elicits higher rates of T‐cell activation in vitro than free antibodies. Importantly, it is demonstrated in two tumor models that combination immunotherapy administered in the form of DINP is more effective than the same regimen administered as free antibodies. This work demonstrates a novel strategy to improve combination immunotherapy using nanotechnology. Abstract : Combination immunotherapy has recently emerged as a powerful cancer‐treatment strategy. However, standard administration of these therapeutics as free antibodies results in suboptimal T‐cell binding events. Precise spatiotemporal codelivery of aPD1 and aOX40 using nanoparticles (dual‐immunotherapy nanoparticles) is shown to result in improved T‐cell activation, enhanced therapeutic efficacy, and increased immunological memory.